КОМУТАЦІЙНІ ПРОЦЕСИ У ТРИФАЗНИХ ТРАНСФОРМАТОРАХ З ТРИПРОВІДНОЮ СИСТЕМОЮ ЖИВЛЕННЯ - Халіков , В.А. (Інститут електродинаміки НАН України, Київ, 2013)
Considered switching processes in the three-phase transformers with various configurations of winding connections in the absence of the power supply system of the neutral conductor. Visual simulation of transient processes is done with MATLAB and proposes measures to minimize the duration of the processes of. Means of visual simulation shows the dependence of decay processes residual magnetic flux in three-phase transformers, depending on the connection scheme. Attention is drawn to that disabling the transformer thyristor switcher accompanied by saturation of its magnetic circuit. Inertial nature of the magnetic flux decline is an obstacle to the next, fast time, connect the transformer to the mains. Patching, a system of three-phase transformer is not expected to reduce the magnetic flux to zero and not allowing inrush current in its windings. Presented a visual model of the proposed switching system and describes in detail the principle of its work. References 5, figures 12.